Christianity in Sub-Saharan Africa: An African Inculturation Hermeneutic - Khosa-Nkatini, Hundzukani P. (UIN Sunan Gunung Djati Bandung, 2022)
Christianity in sub-Saharan Africa has always been a focal point for research, with some contending that the preachers brainwashed Africans when they carried the gospel to them since they neglected to learn Africanism. This stays a discussion among the Evangelical Â Â Presbyterian Church in South Africa (EPCSA) where the creator of this study is a pastor. It has been stated that when a person becomes a Christian, that individual can never again discuss precursors or converse with predecessors, these terms refer to ancestors It is a transgression, while others say nothing bad can really be said about going to chapel yet rehearsing your African convictions and customs. African religion has faith in predecessors and Christianity has confidence in God. In any case, African religion accepts that God exists yet at the same time wants to get assurance from their ancestors. Some contend that there is nothing out of sorts when individuals practice their African convictions because it is not destructive to them or the following individual. Along these lines, African Religion (AR) instructs that it is critical for one to look for available resources to control or control those outer powers and offices that are more remarkable than human comprehension. This is done through ceremonial practices, mystical recipes, and charms endorsed by strict specialists to the individuals who feel compromised. It is inappropriate to expect that all Africans are something similar and that their customs are something similar or practice for similar reasons. Nonetheless, there are similitudes between African societies. Religion ought to assume a basic part in the redefinition of this peculiarity, as devotees haggle between standard regulations and strict rules. This study will analyse the confirmation that Christianity in the sub-Saharan Africa is a peculiarity and that it ought to lead strict synchronization into new world convictions and strict African practices. African Customs, given the circumstances, include exactly the secret of human reality, our individual, our relations with others and with the world. It contacts that reality that is not to be gotten a handle on and which cannot be verified.